Fluorine-Containing Inhalation Anesthetics: Chemistry, Properties and Pharmacology - Wang, Yuzhong; Ming, Xiao-Xia; Zhang, Cheng-Pan (Current Medicinal Chemistry, 2020)
Studies on fluorinated inhalation anesthetics, including synthesis, physical chemistry and pharmacology, have been summarized in this review. Retrospecting the history of inhalation anesthetics revealed their increasing reliance on fluorine and ether structures. Halothane causes a rare but severe immune-based hepatotoxicity, which was replaced by enflurane in the 1970s. Isoflurane replaced enflurane in the 1980s, showing modest advantages (e.g. lower solubility, better metabolic stability, and without convulsive predisposition). Desflurane and sevoflurane came into use in the 1990s, which are better anesthetics than isoflurane (less hepatotoxicity, lower solubility, and/or markedly decreased pungency). However, they are still less than perfect. To gain more ideal inhalation anesthetics, a large number of fluorinated halocarbons, polyfluorocycloalkanes, polyfluorocycloalkenes, fluoroarenes, and polyfluorooxetanes, were prepared and their potency and toxicity were evaluated. Although the pharmacology studies suggested that some of these agents produced anesthesia, no further studies were continued on these compounds because they showed obvious lacking as anesthetics. Moreover, the anesthetic activity cannot be simply predicted from the molecular structures but has to be inferred from the experiments. Several regularities were found by experimental studies: 1) the potency and toxicity of the saturated linear chain halogenated ether are enhanced when its molecular weight is increased; 2) the margin of safety decreases and the recovery time is prolonged when the boiling point of the candidate increases; and 3) compounds with an asymmetric carbon terminal exhibit good anesthesia. Nevertheless, the development of new inhalation anesthetics, better than desflurane and sevoflurane, is still challenging not only because of the poor structure/activity relationship known so far but also due to synthetic issues.
Keywords: anesthetics